Looking for the future - Hope and adolescent risk behaviour in rural KwaZulu-Natal, South Africa - Faith Magut; Natsayi Chimbindi; Kathy Baisley; Thembelihle Zuma; Janet Seeley; Maryam Shahmanesh (Taylor & Francis Group, 2024)
We investigate the relationship between hope and risky behaviour and the role of migration among young people in northern KwaZulu-Natal, South Africa. We use data from a cohort of n = 5248 adolescents and young adults (AYA) aged 13-35 recruited and followed up in 2017-2019. We conducted a structured quantitative survey to assess levels of hope among AYA using a validated tool/scale. 44% of participants were aged 13-17 years, 63% were still in school, 66% were from rural areas, and 26% were from food insecure households. The mean hope total score was 31.7. The mean hope score was lower for females compared to males −0.43(95%CI; −0.64, −0.21) and lower for those out of school and not matriculated compared to those in school −0.72(95%CI; −1.1, −0.32). Young people who had experienced violence had a lower mean hope score than those who had not −0.28(95%CI: −0.50, −0.06). Those out of school, matriculated and unemployed were more likely to migrate than those in school (aOR = 1.60, 95%CI; 1.25, 2.05). AYA who were food insecure were also more likely to migrate (aOR = 1.23, 95%CI; 1.05, 1.43). Our findings suggest a need for structural interventions that address employment and education needs and harmful gender norms for older AYA.